2016
DOI: 10.1016/j.bbabio.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Na + -translocating NADH:quinone oxidoreductase in voltage generation and Na + extrusion in Vibrio cholerae

Abstract: For Vibrio cholerae, the coordinated import and export of Na(+) is crucial for adaptation to habitats with different osmolarities. We investigated the Na(+)-extruding branch of the sodium cycle in this human pathogen by in vivo (23)Na-NMR spectroscopy. The Na(+) extrusion activity of cells was monitored after adding glucose which stimulated respiration via the Na(+)-translocating NADH:quinone oxidoreductase (Na(+)-NQR). In a V. cholerae deletion mutant devoid of the Na(+)-NQR encoding genes (nqrA-F), rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Comparison of the growth behavior of V. cholerae with that of the corresponding nqr deletion strain on mixed amino acids at high salt concentrations revealed that lack of the NQR did not affect initial growth rates but diminished final growth yield (6,13). However, the NQR was mandatory for growth under alkaline, hypoosmotic conditions, and it was demonstrated that the in vivo function of NQR is to maintain the transmembrane voltage rather than to establish a chemical Na ϩ gradient (13). In a suckling mouse model of infection, the persistence of V. cholerae depended on the NQR (14).…”
mentioning
confidence: 99%
“…Comparison of the growth behavior of V. cholerae with that of the corresponding nqr deletion strain on mixed amino acids at high salt concentrations revealed that lack of the NQR did not affect initial growth rates but diminished final growth yield (6,13). However, the NQR was mandatory for growth under alkaline, hypoosmotic conditions, and it was demonstrated that the in vivo function of NQR is to maintain the transmembrane voltage rather than to establish a chemical Na ϩ gradient (13). In a suckling mouse model of infection, the persistence of V. cholerae depended on the NQR (14).…”
mentioning
confidence: 99%
“…The addition of 0.1 mM arabinose to the growth medium resulted in a slight increase in the final cell yield with the reference strain (Fig. 7), perhaps caused by an increase in membrane potential generated by the Na ϩ -NQR (49). Increasing the arabinose concentration to 1 mM and 10 mM did not affect the reference strain but led to a decrease in final cell densities of V. cholerae ⌬oxyR/pNqr1 by 11% (1 mM arabinose) and 26% (10 mM arabinose) compared to V. cholerae/pNqr1 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In many alkaline environments, NQR constructs the primary sodium efflux system through oxidation of NADH and reduction of quinone. This process creates an electrochemical gradient of net negative charge in the cytosol (51), and the gradient is used by cation/proton antiporters ( e.g., Na + /H + , and K + /H + ) to exchange non-balanced movement of positive charge (H + ) to the cell (more protons enter the cytoplasm as compared to the efflux of sodium or potassium ions (49, 51, 52, 53). In a global mapping of soil bacterial communities, cation/proton antiporters were observed to be key genes overrepresented in dryland soil, presumably due to the high levels of salt and pH in arid soils (54).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no prior study has linked environmental microbiome functions to pH level or salinity. However, the association between our significantly differentiated genes to processing specific environmental conditions is established in vitro in numerous studies (51, 63). Here, we hypothesized that differentially abundant genes could be used as predictive markers of environmental cue, and this hypothesis is supported by meta-analyses demonstrating a link between single isolate studies and microbial communities in vivo .…”
Section: Discussionmentioning
confidence: 99%